ICE2019 Conference Proceedings : Education for the 21st century - Siti Aishah Hashim Ali, (Open University Malaysia (OUM), 2019)
The International Conference on Education (ICE 2019) provided an excellent platform for knowledge sharing and networking to explore new opportunities, latest developments and current issues in education. The conference focused on innovation and technology in education, assessment in the 21st century and access to education and lifelong learning.